COGNITIVE CHARACTERISTICS OF 10-13-YEAR-OLDS WITH DIFFERENT PLANNING ACTION TYPES - Fedekin, Igor; Mukhametshin, Azat; Asratyan, Norair (Revista Inclusiones, 2020)
The educational activity theory developed by D.B. Elkonin and V.V. Davydov assumes that children’s theoretical thinking is individualized in the transitional period between primary school age and adolescence age. Theoretical thinking itself is determined by the content operations included – content analysis, planning, and reflection. The article deals with the issue of individual characteristics of theoretical thinking development in early adolescent period. We introduce the idea of the relation between formal and dynamic characteristics of thinking and content thinking operations. Content planning, which is one of the main theoretical thinking operations, is regarded as a factor of its development. The typology of planning action is based on V.V. Davydov’s theory of content generalization and on the two main types of thinking identified by the scientist – the empirical and theoretical types. The theory assumes that theoretical thinking is formed in a primary school when educating according to special programs aimed at learning activity development. The types of planning actions are distinguished according to differentiation-based positions in learning activity.